The Role of Contraction Mode in Determining Exercise Tolerance, Torque-Duration Relationship, and Neuromuscular Fatigue - Ducrocq, Guillaume P; Al Assad, Simon H; Kouzkouz, Nabil; Hureau, Thomas J (Medicine and science in sports and exercise, 2023)
Critical torque (CT) and work done above it ( W ') are key predictors of exercise performance associated with neuromuscular fatigue. The aim of the present study was to understand the role of the metabolic cost of exercise in determining exercise tolerance, CT and W ', and the mechanisms of neuromuscular fatigue. Twelve subjects performed four knee extension time trials (6, 8, 10, and 12 min) using eccentric, isometric, or concentric contractions (3-s on/2-s off at 90°·s -1 or 30°·s -1 ) to modulate the metabolic cost of exercise. Exercise performance was quantified by total impulse and mean torque. Critical torque and W ' were determined using the linear relationship between total impulse and contraction time. Cardiometabolic, neuromuscular, and ventilatory responses were quantified. Neuromuscular function was evaluated by maximal voluntary contraction, resting potentiated single/doublet electrical stimulations, and superimposed single electrical stimulation to quantify neuromuscular, peripheral, and central fatigue, respectively. Compared with isometric exercise, total impulse (+36% ± 21%; P < 0.001), CT (+27% ± 30%; P < 0.001), and W ' (+67% ± 99%; P < 0.001) were increased during eccentric exercise, whereas total impulse (-25% ± 7%; P < 0.001), critical torque (-26% ± 15%; P < 0.001), and W ' (-18% ± 19%; P < 0.001) were reduced in concentric exercise. Conversely, the metabolic response and the degree of peripheral fatigue were reduced during eccentric exercise, whereas they were increased during concentric exercise. Critical torque was negatively associated with oxygen consumption gain ( R2 = 0.636; P < 0.001), and W ' was negatively associated with rates of neuromuscular and peripheral fatigue indices ( R2 = 0.252-0.880; P < 0.001). The contraction mode influenced both CT and W ', and consequently exercise tolerance, indicating that the metabolic cost of contraction played a key role.